Epidemiological analysis of COVID‐19 and practical experience from China. Issue 7 (10th April 2020) - Ye, Qing; Wang, Bili; Mao, Jianhua; Fu, Junfen; Shang, Shiqiang; Shu, Qiang; Zhang, Ting
Abstract: The rapid spread of the epidemic has aroused widespread concern in the international community. Severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2) was first reported in China, with bats as the likely original hosts and pangolins as potential intermediate hosts. The current source of the disease is mainly patients infected with SARS‐COV‐2. Patients in the incubation period may also become sources of infection. The virus is mainly transmitted via respiratory droplets and contact, and the population is generally susceptible. The epidemic has progressed through the local outbreak stage and community transmission stage due to exposure at Wuhan's Huanan wholesale seafood market and is now in the stage of large‐scale transmission due to the spread of the epidemic. The basic productive number (R0) at the beginning of the epidemic was 2.2, with an average incubation period of 5.2 days. The proportion of critically ill patients was 23.4%, the mortality rate was lower than those of SARS and Middle East respiratory syndrome, and 96.5% of deaths occurred in Hubei Province, where the outbreak occurred first. Among them, elderly men with underlying diseases had a higher mortality rate. Chinese medical staff have summarized a set of effective strategies and methods in the diagnosis and treatment of this disease that are worthy of reference for their international counterparts. With powerful government intervention and the efforts of Chinese medical staff, China's outbreak has gradually improved. Research Highlights: The current source of the disease is mainly patients infected with SARS‐COV‐2. Patients in the incubation period may also become sources of infection. The virus is mainly transmitted via respiratory droplets and contact, and the population is generally susceptible. The proportion of critically ill patients was 23.4%, the mortality rate was lower than those of SARS and Middle East respiratory syndrome. Among them, elderly men with underlying diseases had a higher mortality rate.